TRANSLATION AS A CATALYST IN THE DEVELOPMENT OF MODERN CHINESE LEGAL LANGUAGE - Cao, Deborah (Comparative Legilinguistics, 2021)
This paper focuses translation of legal language and the development of modern Chinese legal language as a translated legal language. It first describes the historical contexts in which China underwent enormous and unprecedented social and political changes including changes to law in the late 1800s and early 1900s. It then discusses how translation played an important catalyst role in introducing Western law, legal practices, legal concepts and terminology in the emerging modern Chinese legal language as we know it today, and in the process, lent a helping hand in negotiating China’s transition to modernity through translation and creating a new legal language and legal system. It also considers the issues in translingual and cross-cultural communication and understanding translated Chinese legal language.